Ecology of Mesamphiagrion laterale (Odonata: Coenagrionidae): abundance, reproduction and interactions with co-occurring species (2020)
The behavior of Mesamphiagrion laterale (Selys, 1876) is described based upon 2430 hours of observation. A total of 2820 individuals were observed for 270 days from 2014 to 2015 using mark-recapture. Probabilities of resight, highest reproductive activity, time-perch and time of perch-temperature were statistically analyzed. Mesamphiagrion laterale is not a territorial species, the individuals perch on grass, trees, garbage, ground, and rocks, they feed on hemipterans, mosquitoes, spiders and other damselflies, and are prey to spiders and birds. Conspecific siege and interspecific interactions by perch were observed. No courtship was observed. During tandem, which lasted for 3–90 min, the ventral side of the male’s abdominal segment 2 was in contact with the female’s abdominal segments 8–10 until a wheel was formed. We observed three tandem pair combinations: sexually mature males and females, immature males with mature females, and immature males and females. While copulation lasted from 7 to 20 min, oviposition lasted from 12 to 15 min. Irrespective of male presence, oviposition occurred in submerged or emerged areas of Eichornia crassipes. We recorded the highest reproductive activity between 12:00 and 12:35 (Colombia Time-COT, UTC-5). Above 20°C, a larger perching area close to the water allows more reproductive events. However, a more extensive canopy cover impedes achieving optimal reproductive temperatures. Species interactions within this community may be explained by temporal and spatial niche partitioning.